Business Intelligence Capabilities and Firm Performance: Empirical Study on PT. Erlangga Mahameru Publishers - Piqri, Mochammad; Suyoso, Aldo Lovely Arief (Manunggal Halim Jaya, 2024)
This research aims to analyze the influence of business intelligence on firm performance. Erlangga Mahameru Publishers. Using quantitative explanatory methodology, the study utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS), which was used in this work via SmartPLS software. A structured survey was used to gather information from 156 workers in PT. Erlangga Mahameru Publishers. The findings reveal a positive relationship between business intelligence and firm performance. There is a positive relationship between sensing capability and transforming capability, with a path coefficient of 0.877. There is a positive relationship between transforming capability and driving capability, with a path coefficient of 0.904. A positive relationship exists between driving capability and firm performance, with a path coefficient of 0.828.